Closing the gaps: phylogenetic relationships in the Brassicaceae based on DNA sequence data of nuclear ribosomal ITS region - Warwick, Suzanne I.; Mummenhoff, Klaus; Sauder, Connie A.; Koch, Marcus; Al-Shehbaz, Isan Ali (Plant systematics and evolution, 2010)
Sequence data from the nuclear encoded ribosomal internal transcribed spacer (ITS) region were used to determine monophyly of tribes, tribal limits, and tribal relationships of 96 so far unassigned or tentatively assigned genera (represented by 101 taxa/accessions) within the Brassicaceae. ...
Gesehen am 11.10.2023